Peran Moderasi Dewan Komisaris Independen dan Auditor External Dalam Hubungannya Diantara Pengungkapan Akuntansi Lingkungan dan Nilai Perusahaan - Madinah, Dina (Universitas Muhammadiyah Malang, 2024)
Research objective: To provide empirical evidence of independent boards of commissioners and external auditors in moderating the influence of environmental accounting disclosures on firm value. Method/approach: This research uses multiple regression analysis and purposive sampling method with the sample criteria being firms that take part in the environmental management assessment of the Ministry of Environment and Forestry. A total of 112 companies in 2021 and 2022 were used from various sectors except the financial sector. Results: Environmental accounting disclosures, company size, profitability and audit committee were found to have no influence on company size. Meanwhile, the independent board of commissioners and the big four external auditors were found to have an influence on environmental accounting disclosures, however only the independent board of commissioners could moderate the influence of environmental accounting disclosures on firm value. Practical implications: Independent boards of commissioners in natural resource, service and manufacturing firms have exercised their independence as proven by being able to moderate the influence of the spread of environmental accounting on firm value. This may attract the attention and investment interest of investors and stakeholders. Originality/novelty: Making the independent board of commissioners and external auditors as moderating variables, adds evidence to agency theory that simply giving power and appointing firm management is not enough but the independent board of commissioners must carry out independent supervision so that it can increase firm value.